Recruiting employees : individual and organizational perspectives - Barber, Alison E. (Foundations for organizational science., 1998)
Introduction ---- Generating Applicants ---- Maintaining Applicant Status ---- Influencing Job Choice ---- Does Recruitment Matter? The Organization's Perspective ---- Toward an Agenda for Recruitment Research.